(untitled) (Faridpur Medical College Journal, 2015)
Sturge-Weber syndrome sometimes referred to as encephalotrigeminal angiomatosis, is a rare congenital neurological and skin disorder. This is case report of 7 years old mentally disabled boy, with long-standing seizures, with a portwine nevi on the right side of the face along the distribution of trigeminal nerve. Interictal encephalogram showed bilateral slow activity, pronounced in the right hemisphere, with epileptogenic activity in the right fronto-parietal region. Computerized tomography and magnetic resonance imaging showed intracranial calcifications and atrophy of the right hemisphere of brain. Professional counseling and support in addition to drug treatment provide help to patients and their family to overcome their problems and improve the treatment outcome. Faridpur Med. Coll. J. 2014;9(2): 102-104